2001
DOI: 10.1097/00001756-200102120-00035
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal, parahippocampal and occipital-temporal contributions to associative and item recognition memory: an fMRI study

Abstract: The temporal lobe regions involved in memory retrieval were examined using fMRI. During an associative recognition test, participants made memory judgments about the study color of previously presented drawings of objects, and during item recognition tests they made old/new judgments about previously studied objects or new objects. Associative recognition compared with old item recognition led to activations in bilateral hippocampal and parahippocampal regions, as well as in the left middle occipital gyrus. Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
132
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(158 citation statements)
references
References 22 publications
21
132
3
2
Order By: Relevance
“…The results of the PPI analyses revealed that, in healthy older participants (and not in AD+ patients), the inferior precuneus/PCC was functionally connected to the hippocampus, the inferior parietal cortex and the DLPFC specifically during successful controlled retrieval of the association. The hippocampus has been found to be engaged during retrieval of word pairs (Giovanello et al, 2004(Giovanello et al, , 2009Meltzer and Constable, 2005;Prince et al, 2005;Stark and Squire, 2001), face-name associations (Kirwan and Stark, 2004;Small et al, 2001), face-object associations (Ranganath et al, 2004a), face-spatial location associations (Duzel et al, 2003) and retrieval of an item with its learning context (Slotnick, 2010;Yonelinas et al, 2001). These findings support the idea that the hippocampus plays a role in the use of relational information in declarative memory (Preston et al, 2004).…”
Section: Functional Connectivity During Associative Cermentioning
confidence: 68%
“…The results of the PPI analyses revealed that, in healthy older participants (and not in AD+ patients), the inferior precuneus/PCC was functionally connected to the hippocampus, the inferior parietal cortex and the DLPFC specifically during successful controlled retrieval of the association. The hippocampus has been found to be engaged during retrieval of word pairs (Giovanello et al, 2004(Giovanello et al, , 2009Meltzer and Constable, 2005;Prince et al, 2005;Stark and Squire, 2001), face-name associations (Kirwan and Stark, 2004;Small et al, 2001), face-object associations (Ranganath et al, 2004a), face-spatial location associations (Duzel et al, 2003) and retrieval of an item with its learning context (Slotnick, 2010;Yonelinas et al, 2001). These findings support the idea that the hippocampus plays a role in the use of relational information in declarative memory (Preston et al, 2004).…”
Section: Functional Connectivity During Associative Cermentioning
confidence: 68%
“…Increased ER firing to repeats has been observed in monkeys when the repeated stimuli are also the behavioral targets (Suzuki et al, 1997). Some hemodynamic studies have found specific medial temporal activation during intentional recall and experiential recognition over implicit repetition, and lesion studies have found a specific deficit after medial temporal lesions in the same circumstances (Yonelinas et al, 2001;Yonelinas et al, 2002), but both findings are inconsistent (Squire et al, 2004). A variety of evidence in animals has led to the suggestion that familiarity/recognition depends on the repetition-induced decreases in cell firing in more lateral neocortical segments of the ventral temporal lobe, whereas conscious retrieval and recollection depends on medial structures, and especially the HC (Brown and Aggleton, 2001).…”
Section: Repetition and Retrieval Effectsmentioning
confidence: 99%
“…FMRI recall task-Associative memory recall tasks done during functional MRI scanning have repeatedly been shown to result in robust activation of the hippocampal formation (e.g., Killgore 2000;Sperling et al 2001;Stark and Squire 2001;Yonelinas et al 2001;Duzel et al 2003;Sperling et al 2003;Giovanello et al 2004). These studies, and others, document both the role of the hippocampus in recall tasks and the ability of fMRI to measure the functioning of the hippocampus during such tasks.…”
Section: Brain Volume and Functionmentioning
confidence: 99%
“…To evaluate the activity of the hippocampus during a recall task, we followed a design similar to that used by Yonelinas et al (2001). Twenty-four hours before the MRI session, participants were presented with 244 line drawings from the Snodgrass set of pictures (Snodgrass and Vanderwart 1980).…”
Section: Brain Volume and Functionmentioning
confidence: 99%